Ceramide is More Effective than Shea Butter in Maintaining Skin Acidity - Zilpa Widyastuti; Suci Widhiati (Faculty of Medicine, Universitas Airlangga, 2022)
Background: Skin is the largest organ that functions as a physical barrier. Stable skin pH can maximize its function. Ceramide and shea butter cream have components that maintain the skin pH in the stratum corneum. Purpose: The aim is to compare ceramide and shea butter cream effects on skin pH. Methods: The experimental analytic study was performed on 30 respondents. The skin pH measurement was done before applying creams and 30 days after applying ceramide cream and shea butter cream. Ceramide cream was applied on the right volar and shea butter cream on the left volar. Comparative analysis with a paired t-test was used with a significant value of p<0.05. Results: The average skin pH after applying ceramide cream was 4,61±1,19, while shea butter cream was 5,30±1.07. The derivation of skin pH after ceramide cream application was 1,57±1,26, and that of shea butter cream was 0,88±1,14. The application of ceramide cream showed a lower pH than shea butter cream significantly, with p=0.025. Conclusion: The intervention using ceramide and shea butter cream for 30 days could lower the skin pH level. The derivation of skin pH with ceramide is more significant than using shea butter cream. Ceramide can be considered to maintain skin homeostasis and skin pH.